2021
DOI: 10.1101/2021.03.18.21253907
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated immunovirological profiling validates plasma SARS-CoV-2 RNA as an early predictor of COVID-19 mortality

Abstract: Despite advances in COVID-19 management, it is unclear how to recognize patients who evolve towards death. This would allow for better risk stratification and targeting for early interventions. However, the explosive increase in correlates of COVID-19 severity complicates biomarker prioritisation. To identify early biological predictors of mortality, we performed an immunovirological assessment (SARS-CoV-2 viral RNA, cytokines and tissue injury markers, antibody responses) on plasma samples collected from 144 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 60 publications
(89 reference statements)
0
22
0
Order By: Relevance
“…In animal models of COVID-19, mutation of monoclonal antibodies leading to loss of Fc-mediated function, but sparing the neutralizing function, abrogated the protective effect of the antibody [22][23][24][25] . In cohort studies of severe COVID-19, low Fc-mediated function, but not neutralization, was associated with mortality 26,27 .…”
Section: Discussionmentioning
confidence: 96%
“…In animal models of COVID-19, mutation of monoclonal antibodies leading to loss of Fc-mediated function, but sparing the neutralizing function, abrogated the protective effect of the antibody [22][23][24][25] . In cohort studies of severe COVID-19, low Fc-mediated function, but not neutralization, was associated with mortality 26,27 .…”
Section: Discussionmentioning
confidence: 96%
“…Further, the inflammation marker C can also be applied to patient data, similar to other proposed metrics (e.g. CytoScore [68]).…”
Section: Discussionmentioning
confidence: 99%
“…Models by design require simplifying complex dynamics to highlight critical underlying structures, which should then be experimentally or clinically verified. For instance, some unmodeled cytokines have overlapping function and cellular sources to those explicitly modelled here; thus, model predictions may be representative of broader synergistic effects [68] and other cytokines could also be targets of interest. Also, as this work is focused on acute, primary infections, our model does not account for antibody production and we chose not to explore questions related to vaccination efforts nor the potential for cross-reactivity given exposure to other seasonal coronaviruses.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…However, we note that results as obtained in this study are very similar to those observed in larger cross-sectional and longitudinal studies. 3,5,6 Furthermore, although we successfully used our ADCC assay to show the importance of Fc-mediated effector functions of neutralizing Abs to protect from lethal SARS-CoV-2 challenges in K18-hACE2 transgenic mice 42 and as an immune correlate for survival in acutely infected individuals, 43 our assay uses cells constitutively expressing the Spike proteins and not bona fide SARS-CoV-2-infected cells.…”
Section: Limitations Of Studymentioning
confidence: 99%